Local structure formation in alkyl-imidazolium-based ionic liquids as revealed by linear and nonlinear Raman spectroscopy - Iwata, Koichi; Okajima, Hajime; Saha, Satyen; Hamaguchi, Hiro-O (My University, 2007)
We show several pieces of Raman spectroscopic evidence that are indicative of local structure formation in imidazolium-based ionic liquids. Low-frequency Raman spectra of C(n)mimX, where C(n)mim stands for 1-alkyl(CnH2n+1)-3-methylimidazolium cation and X represents the anion, exhibit broad bands assignable to collective modes of local structures. Spatial distributions of coherent anti-Stokes Raman scattering (CARS) signals from C(n)mim[PF(6)l are consistent with local structures whose size increases with increasing n. Picosecond Raman spectra of S, trans-stilbene as a "picosecond Raman thermometer" show microscopic thermal inhomogeneity ascribable to local structure formation in C(2)mimTf(2)N and C(4)mimTf(2)N. We also describe two novel phenomena that we believe are relevant to extraordinary nanoenvironments generated by local structures in a magnetic ionic liquid C(4)mim[FeCl4].